Intermediate to Long Term Clinical and Radiographic Outcomes of Triple Arthrodesis: A 422 Case Retrospective Review. Issue 4 (16th October 2019) - King, Jesse; Henrikson, Karl; Harper, Thomas; Anderson, Mike; Stauch, Chris; Juliano, Paul; Aynardi, Michael
Category: Ankle Arthritis, Hindfoot Introduction/Purpose: Triple arthrodesis is a commonly performed surgical treatment for hindfoot arthritis and deformity. No study has clearly delineated correlates of both clinical and radiographic outcomes in a sample size this large. The purpose of this study is to explore predictive and demographic outcome measures with long-term followup after triple arthrodesis. Methods: With IRB approval, an institutional radiology database was queried for patients undergoing triple arthrodesis between 2004 and 2016, by a single surgeon at a single institution. A total of 465 cases were identified. Pre- and post-operative clinical and radiographic data was collected retrospectively. Demographic and predictive data included: age, Body Mass Index (BMI), American Society of Anesthesiologists Score (ASA), Charleston Comorbidity Index (CCI), diabetic status, osteoporosis, hypothyroidism, and neuromuscular disease status. Clinical outcomes including infection rate, reoperation rate and clinical nonunion were recorded. Unintended return to the operating room defined clinical failure. Radiographic data including non-union rate, pre- and post- operative ankle degenerative joint disease was also recorded. Statistical analysis was then performed to evaluate the relationship between predictive measures and various outcomes including reoperation, infection, and non-union rates. 23 cases were lost to follow-up. Results: A total of 442 feet (397 patients) were analyzed. The average age was 54 years (14 to 85) with the majority of cases being female (60%). Average follow up was 593 days (40 to 4079). Overall failure rate was 13.7% with clinical nonunion rate of 4.5%. Infection rate was 5.9%. Mortality rate was 0% at 2 years post-operatively. Predictors of failure included: increased BMI, elevated ASA, history of diabetes, underlying neuromuscular disorder (Figure 1). We found no significant difference between pre and post-operative degenerative joint disease rates in the midfoot (9.4%, 12.5%) and ankle (11.7%, 13.7%), respectively. Conclusion: Triple arthrodesis is a highly effective procedure for treating hindfoot arthritis. Certain predictive measures including BMI, ASA score, diabetic status and underlying neuromuscular disorders significantly correlate with radiographic union. Additionally, diabetic status significantly correlates with infection status postoperatively. An understanding of these predictive measures may help surgeons in their preoperative planning to improve their clinical and radiographic success rates.